2022
DOI: 10.3390/v14010122
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Combined Antiretroviral Therapy on Metabolic Syndrome Components in Adult People Living with HIV: A Literature Review

Abstract: The development of metabolic derangements as a result of HIV treatment has been an important area of research since the introduction of zidovudine in the 1980’s. Antiretroviral therapy has intensely evolved in the last three decades, with new drugs gradually incorporated into everyday clinical practice. With the life expectancy of people living with HIV rapidly approaching that of their HIV-negative counterparts, the influence of these antiretrovirals on the development of the components of the metabolic syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 94 publications
(135 reference statements)
0
29
0
Order By: Relevance
“…ART may also play a direct role in lipid dysregulation in brain as its adverse impact on metabolism is well characterized. Systemically, it is well established that ART causes a mean weight gain of 3-7 kg within the first year of initiating treatment (86)(87)(88)(89). Further, specific ART drugs or ART classes can have varying impacts on circulating lipid levels, blood pressure, and risks for developing metabolic syndromes, including diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ART may also play a direct role in lipid dysregulation in brain as its adverse impact on metabolism is well characterized. Systemically, it is well established that ART causes a mean weight gain of 3-7 kg within the first year of initiating treatment (86)(87)(88)(89). Further, specific ART drugs or ART classes can have varying impacts on circulating lipid levels, blood pressure, and risks for developing metabolic syndromes, including diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 27, 2022. ; https://doi.org/10.1101/2022.09.26.508302 doi: bioRxiv preprint after changing regimens from older protease inhibitors (86,96). Hypertension, another disorder related to lipid dysregulation, is also more prevalent in individuals receiving ART.…”
Section: Discussionmentioning
confidence: 99%
“…HIV is associated with chronic inflammation and immune activation, leading to decreased levels of total cholesterol and HDL-C and increased levels of LDL-C and triglycerides [ 23 24 ]. Dyslipidemia has been suggested to be associated with age, sex, genetic factors, and lifestyle, including diet [ 25 ].…”
Section: Dyslipidemia and Artmentioning
confidence: 99%
“…The proportion of women enrolled in this study was too small (2.9% of the whole cohort) and it was difficult to apply the findings to newer ARTs. Hence, it was possible that the effects of weight gain on mortality, especially among women, were not examined properly [ 25 ]. Therefore, further long-term research is needed to clarify the clinical impact of ART-associated weight gain on the development of CVDs, diabetes mellitus, and mortality, especially among Korean PLWH.…”
Section: Weight Gain and Artmentioning
confidence: 99%
“…Consequently, the life expectancy and the quality of life among the people living with HIV have since improved ( Barbier et al, 2020 ). Despite the benefits of HAART, its long-term use and systemic exposure has been strongly linked with various metabolic disturbances such as diabetes and cardiovascular diseases ( Nansseu et al, 2018 , Sapula et al, 2022 ). Previous studies have reported that initiation of HAART increases the risk of diabetes mellitus ( Nansseu et al, 2018 , Ergin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%